Eros and the nature of 'interest' - Carolyn N. Biltoft (Finance and Society, 2023)
In Greek archaic literature and philosophy, Eros, the god of love and desire, has numerous origin stories, which lead to different understandings of his nature. These extend to both orthodox and heterodox texts within the economic canon, whose definitions of interest rearticulate the mythological subtext of desire. What might have happened if the Western world had not discarded the passions in its quest for material progress?
Keywords: 300; Albert Hirschman; desire; Eros; interest; passions; usury